Preferences for literary and scientific texts according to the university degree - Sánchez Bejerano, Lucía; Pérez Fernández, Lucila María; Griffin, Kim Lori (Didáctica. Lengua y Literatura, 2022)
This article shows a study carried out at the European University of the Atlantic, Santander. The main goal is to discover the preference for literary and informative texts according to the university degree that students are taking. The sample of the study was of n=193 students from the first year in several degrees from the Faculty of Health Sciences, Faculty of Social Sciences and Humanities, and the Polytechnic University. To analyse it, a questionnaire was designed ad hoc to gather students’ opinions regarding their preferences in literary or informative texts, being the scientific text among them. The questionnaire was applied with Google Forms. After a contrast analysis with the H of Kruskal-Wallis test and a post hoc U of Mann-Whitney test, results showed that preferences for science-fiction, romance, tourism and travelling, science, sports/ health, music, classic literature, and poetry had significant differences among the university degrees. Students from the Faculty of Social Sciences and Humanities were the ones with a lower interest in scientific reading and, surprisingly, students from the Psychology degree did not seem to care for health reading. This makes the researches study and contrast the lack of interest of scientific and academic reading with other similar investigations. Finally, we found that students show a similar interest for adventure, mystery, history/ politics, comedy, thrillers, and biographies. According to these results, the main objective was obtained. Consequently, some future lines for research are discussed to help university teachers selecting an appropriate literature regarding students’ profile depending on the university degree. Similarly, some research on prereading activities is suggested for those teachers who want to work on scientific or academic literature in the classroom. This could help students to maintain a better consideration on this type of literature.